Strategy in Resolving the DI/TII Rebellion in Aceh, 1953-1959 - Indah Munadia; Mawardi Umar (Universitas Syiah Kuala, 2022)
The research, entitled Military Strategy in Resolving the DI/TII Rebellion in Aceh in 1953-1959, aims to (1) describe the implementation of any military strategy used in resolving the DI/TII rebellion in Aceh, (2) explain the impact of the enactment of military-assisted regions. (Militaire Bijstand) and the Application of the Conceptual Wise Principle to the settlement of the DI/TII rebellion in Aceh in 1953-1959. This study uses a qualitative approach with the help of historical methods. The data collection techniques were carried out through documentation, literature review, and interviews. The results obtained from this study are (1) The implementation of Military Assisted Regions (Militaire Bijstand) became the first strategy to be implemented by sending troops and armed equipment to secure conditions in Aceh, then the next military strategy was implemented called the Wise Principle Concept which became a new beginning for settlement of the rebellion in Aceh. The success of this conception was finally proven by the establishment of the Lamteh Pledge agreement, (2) Development after the completion of the DI/TII rebellion occurred from various sectors in Aceh.